1990
DOI: 10.3133/ofr90523
|View full text |Cite
|
Sign up to set email alerts
|

Late Cretaceous pollen from the Salinian(?) suspect terrane at Pigeon Point, San Mateo County, California

Abstract: The Companion to Maastrichtian Pigeon Point Formation is confined to southwestern San Mateo County, California; the formation is spatially isolated from similar Upper Cretaceous sedimentary rocks. The basement on which the formation rests is not exposed, but the Pigeon Point block is thought by most authors to be part of the Salinian suspect terrane. Reconstructions based on paleomagnetic data have indicated that the Pigeon Point block originated at the continental margin and was then transported some 2,500 km… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
2
0
0
Order By: Relevance
“…A palynologic study by Frederiksen (1990) suggested that the Pigeon Point Formation was deposited at a latitude south of the present United States, which is consistent with the paleontologic studies.…”
Section: Paleontology and Palynologysupporting
confidence: 78%
See 1 more Smart Citation
“…A palynologic study by Frederiksen (1990) suggested that the Pigeon Point Formation was deposited at a latitude south of the present United States, which is consistent with the paleontologic studies.…”
Section: Paleontology and Palynologysupporting
confidence: 78%
“…These tonalites could have provided part of the detritus to the accretionary area at The paleolatitude inferred by location PP1 satisfies the warm--temperate to subtropical climate required by the molluscan assemblages (Elder and Saul, 1993) and is also consistent with the latitude suggested by palynological studies Frederiksen (1990). It is too far north to support the paleomagnetic restoration suggested by Whidden et al (1998).…”
Section: Speculative Reconstructionsupporting
confidence: 54%